The Essential Jung : Selected and introduced by Anthony Storr - Jung, C. G. (Carl Gustav), 1875-1961 (Book collections on Project MUSE., 2013)
In this compact volume, British psychiatrist and writer Anthony Storr has selected extracts from Jung's writings that pinpoint his many original contributions and relate the development of his thought to his biography. Storr's explanatory notes and introduction show the progress and coherence of Jung's ideas. These notes link the extracts, and with Dr. Storr's introduction, they show the progress and coherence of Jung's ideas, including such concepts as the collective unconscious, the archetypes, introversion and extroversion, individuation, and Jung's view of integration as the goal of the.